¿Una república católica dividida? La disputa eclesiológica heredada y el liberalismo ascendente en la independencia de México - Connaughton, Brian (El Colegio de México, A.C., 2010)
The Independence of Mexico found a country furrowed by religious divisions which became immediately noticeable in the republic  created in 1824. The 1826 Senate report  on the Real Patronato expressed the prevailing tensions and the different disturbing facets they presented  to a Catholic  state. The controversy had many dimensions, both domestic and international, and revealed the existence of an intense ecclesiologic debate bringing together  thinkers  and politicians  from both  sides of the Atlantic. This paper mainly underlines the role played by the failure of Spain’s liberal Triennium (1820-1823) and Spanish critics to stir up Mexican perception of the dangers that the Catholic  hierarchy and the Holy See represented for a Catholic state. The author suggests the need to consider  how this confrontation, handled with amazing self-assurance by Mexican ecclesiastical authorities, resulted directly from the tense relations between the Spanish monarchy and the Vatican throughout the eighteenth century.